2017
DOI: 10.1111/dar.12455
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and disadvantaged men: A feasibility trial of an intervention delivered by mobile phone

Abstract: Introduction and AimsDisadvantaged men suffer substantial harm from heavy drinking. This feasibility study developed and evaluated the methods for a trial of a brief intervention delivered by text messages to disadvantaged men. It aimed to test the methods for recruitment and retention, to monitor engagement with the intervention and assess the overall acceptability of study methods.Design and MethodsDisadvantaged men aged 25–44 years who had ≥2 episodes of binge drinking (≥8 units in one session) in the prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…The target sample size for the trial was 798 participants. Our prior feasibility study showed that 57% of disadvantaged men consumed > 8 units of alcohol on at least three occasions during the previous 28 days . A systematic review reported that face‐to‐face alcohol brief interventions resulted in an 11% difference in binge drinking frequency .…”
Section: Methodsmentioning
confidence: 99%
“…The target sample size for the trial was 798 participants. Our prior feasibility study showed that 57% of disadvantaged men consumed > 8 units of alcohol on at least three occasions during the previous 28 days . A systematic review reported that face‐to‐face alcohol brief interventions resulted in an 11% difference in binge drinking frequency .…”
Section: Methodsmentioning
confidence: 99%
“…108 Moreover, HAPA has successfully informed the content of previous NIHR-funded SMS-delivered interventions. [108][109][110] The weight loss aspect of the intervention was shaped by the specific behaviour change phases encompassed by HAPA, including the motivational and volitional phases. The specific psychological processes to increase motivation include outcome and risk perceptions, as well as task self-efficacy (i.e.…”
Section: Identifying/developing Appropriate Theorymentioning
confidence: 99%
“…Text message programs [55][56][57] used short message service (SMS) to send harm reduction messages related to substance use to participants. While some text-based programs were person-assisted, where an in-person brief intervention was supplemented with two-way text message goal planning, others were more directed by technology, with participants receiving pre-programmed messages on personal control and behavioural change [55,56]. The text message programs primarily focused on brief alcohol interventions for socioeconomically disadvantaged men or for men and women on college and university campuses [56,57].…”
Section: Text Messagementioning
confidence: 99%
“…The text message programs primarily focused on brief alcohol interventions for socioeconomically disadvantaged men or for men and women on college and university campuses [56,57]. In the studies with men who were socioeconomically marginalized, the men in the intervention group tended to engage at high levels with the program and appeared to be more comfortable in regards to divulging sensitive personal information about their relationships and experiences with harmful drinking with this format compared to others [55,56]. In the mixed-gender campus study, setting drinking-limit goals via SMS were found to promote a decrease in drinking particularly for men in comparison to women [57].…”
Section: Text Messagementioning
confidence: 99%